East Java Province: Economic structure and forecast GRDP analysis - Fitri Juniwati Ayuningtyas; Ismadiyanti Purwaning Astuti; Dimas Imam Apriliawan; Kai Shi (Universitas Ahmad Dahlan, 2023)
Most of the sectors affected by the Covid-19 pandemic caused economic growth to decline. The sectors involved are not only the health sector but also the economy, especially trade, industry, and tourism. The research aims to identify the leading sectors, know the characteristics of the pattern and structure of the economy East Java Province. The method analysis used in this research is Location Quotient, Klassen typology, Shift-Share, and linear trend. The findings of this study are: (1) Industrial Sector Processing, Water Supply, Waste Management, Waste and Recycling, Wholesale and Retail Trade; Car and Motorcycle Repair, Provision of Accommodation and Food and Drink, and Information and Communication are the leading sectors that can encourage economic development in East Java Province; (2) Industrial Sector Processing, Water Supply, Waste Management, Waste and Recycling, Wholesale and Retail Trade; Car and Motorcycle Repair, Transportation and Warehousing, Provision of Accommodation and Food and Drink, Information and Communication, Financial and Insurance Services, Educational Services, Health Services and Social Activities are potential sectors in producing production to meet local demand; (3) The manufacturing industry sector is the sector that provides the largest contribution to the GRDP of East Java Province.